The Effect of Professional Training, Job Market Considerations, and Work Environment on Accounting Students' Interest in Careers to be Public Accountants - Oktaviani, Shindy Asri; Diana, Apry Linda (Research of Accounting and Governance, 2023)
Interest is one of the considerations for students in the career selection process. A person's interest can be seen from several internal and external factors. This study aimed to determine the effect of professional training, labor market considerations, and work environment on the interest of STEI Jakarta Accounting Students to become Public Accountants. The research method is a descriptive quantitative approach, measured using multiple linear regression-based methods processed with SPSS Version 26.00. The population in this study were undergraduate students majoring in Accounting STEI Jakarta class of 2018 semester eight, who had followed the Auditing 1 and Audit 2 courses. Using the Slovin formula, the number of samples was 75 respondents by determining the sample's criteria. The results showed that professional training had no significant effect on accounting students' interest in having a career as a public accountant. In comparison, the consideration of the labor market and work environment significantly affects the interest of accounting students in a career as a public accountant